Recollection of children following intensive care. Issue 5 (1st November 2000) - Playfor, S; Thomas, D; Choonara, I
Abstract : BACKGROUND AND AIMS: The recollections of critically ill children following discharge from the paediatric intensive care unit (PICU) have not previously been described. We have interviewed such children to establish the nature of their recollections. METHODS: Children aged 4 years and above were interviewed following discharge from the PICU at the Queens Medical Centre, Nottingham, either in hospital or at home, using a semistructured interview. Their recollections were recorded and interpreted by content analysis. RESULTS: A total of 38 interviews were carried out; 44 specific recollections were reported, the majority being neutral (60%) or positive (25%). Only 15% of recollections were negative. Negative recollections related to aspects of medical care and environmental factors. No child treated with neuromuscular blocking agents remembered any period of therapeutic paralysis. CONCLUSIONS: Children's recollections of PICU are mainly neutral or positive. Mechanically ventilated children sedated with midazolam and morphine remember little of endotracheal intubation.